Halogen and hydrogen bonding host structures for anion recognition and ternary complexes for modulating luminescent output - Hess, A (2016)
This thesis describes the synthesis and anion recognition properties of a series of halogen and hydrogen bonding acyclic and interlocked host receptors and the use of the inclusion supramolecular chemistry of cucurbit[n]uril derivatives in switchable luminescent output. Chapter 1 introduces the field of anion supramolecular chemistry and the properties of cucurbit[n]uril macrocycles which pertain to the research detailed in subsequent chapters. Chapter 2 describes the synthesis and anion recognition properties of a new class of chelating, halogen and hydrogen bonding host molecules. The halogen bonding enhanced selectivity for the Br- anion is demonstrated. Chapter 3 probes the anion recognition characteristics of a series of novel halogen and hydrogen bonding motifs. Evidence for intramolecular hydrogen bond enhanced halogen bonding recognition of halides is presented and the selective recognition of the anion H2PO4- by a [3]rotaxane host is displayed. Chapter 4 discusses the redox-mediated modulation of the luminescent output of a series of visible and near-infrared emitting lanthanide complexes within cucurbit[8]uril based ternary complexes. Chapter 5 describes the experimental procedures and characterisation of the compounds presented in Chapters 2-4. Chapter 6 summarises the conclusions of this thesis.